The house on Mango Street - Cisneros, Sandra (New York : Vintage Contemporaries, 1991)
A young girl living in a Hispanic neighborhood in Chicago ponders the advantages and disadvantages of her environment and evaluates her relationships with family and friends.
Wilson's Senior High School, November 1997
Wilson's Junior High School, September 1995
Wilson's Fiction, January 1996
Teacher Librarian
Multicultural Review, December 1997
Adult
Keywords: Hispanic Americans -- Fiction; Girls -- Fiction; Bildungsromans; Chicago (Ill.) -- Fiction; Bildungsromane